Exploring Narratives of Energy Reliability in Iqaluit, Nunavut - Little, Kaylia (Anthropologica)

(untitled) (University of Victoria, 2025)
Reliability is an important feature of energy infrastructure. In Nunavut, reliability is impacted by the remote, isolated, and independent nature of the energy infrastructure. For Iqaluit, community members view energy reliability through numerous lenses, contexts, and narratives. Perceptions of reliability are examined from the perspective of relative reliability and the contrasting perspective of unreliability. This article explores these narratives to better understand how Iqalummiut view reliability. Respondents were drawn from recent and long-term residents of Iqaluit. Furthermore, this article begins a discussion about how this might be important for both the present and future of the city’s energy infrastructure.